2017
DOI: 10.5194/hess-21-5693-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high spatial and temporal resolution Earth observations on simulated hydrometeorological variables in a cropland (southwestern France)

Abstract: Abstract. Agricultural landscapes are often constituted by a patchwork of crop fields whose seasonal evolution is dependent on specific crop rotation patterns and phenologies. This temporal and spatial heterogeneity affects surface hydrometeorological processes and must be taken into account in simulations of land surface and distributed hydrological models. The Sentinel-2 mission allows for the monitoring of land cover and vegetation dynamics at unprecedented spatial resolutions and revisit frequencies (20 m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Using a coarser spatial resolution, beyond neglecting ecosystem spatial heterogeneity, can potentially also affect the overall mean in the domain and thus the large‐scale fluxes (Pappas et al, ). The presented results reinforce several recent studies that have demonstrated the potential of high‐resolution simulations in better capturing ecohydrological dynamics under current or future conditions (Etchanchu et al, ; Le & Kumar, ; Passalacqua et al, ), especially when identification of patterns is sought.…”
Section: Discussionsupporting
confidence: 87%
“…Using a coarser spatial resolution, beyond neglecting ecosystem spatial heterogeneity, can potentially also affect the overall mean in the domain and thus the large‐scale fluxes (Pappas et al, ). The presented results reinforce several recent studies that have demonstrated the potential of high‐resolution simulations in better capturing ecohydrological dynamics under current or future conditions (Etchanchu et al, ; Le & Kumar, ; Passalacqua et al, ), especially when identification of patterns is sought.…”
Section: Discussionsupporting
confidence: 87%
“…The LAI estimation is also well known to saturate (Veloso et al, 2012). But above a certain threshold, the difference between satellite-estimated and real LAI does not affect significantly the evapotranspiration flux (Etchanchu et al, 2017). The estimated LAI may also differ between sensors.…”
Section: Limitations and Perspectivesmentioning
confidence: 98%
“…As the phenological cycle is determinant in the irrigation management, a LAI climatology is not sufficiently accurate in our study. Hence determining the LAI from high resolution satellite imagery allows taking the actual crop cycle into account in the model (Etchanchu et al, 2017).…”
Section: Satellite Leaf Area Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAO-56 method (Allen et al, 1998) is the most widely used land-surface model, in which the potential evapotranspiration (ET) is adjusted with a crop coefficient and a stress coefficient. The classical method uses standard values of crop coefficient, that implies standard growth conditions, but an increasing number of studies replaces them with remote sensing data (Saadi et al, 2015;Etchanchu et al, 2017;Battude et al, 2017;Yousaf et al, 2021;Kharrou et al, 2021;Maguire et al, 2022), in order to account for the current year conditions. In particular, Etchanchu et al (2017) highlight the contribution of remote sensing data at plot scale, that makes more robust calculation of LAI (leaf area index) and ET in comparison to the classical method.…”
mentioning
confidence: 99%